Contradiction through the ages : interplay of politics in literature and reality in light of nineteen eighty-four and The Hunger Games - Tasnim, Zerin (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.